Evaluation of the antibacterial effect of Echium amoenum Fisch. et Mey. against multidrug resistant Acinetobacter baumannii strains isolated from burn wound infection - Sabour, Mandana; Hakemi Vala, Mojdeh; Mohammadi Motamed, Said; Eiji, Misagh (Novelty in Biomedicine, 2015)
Introduction and aims: Acinetobacter baumannii in recent decay has become an increasing concern in hospitals for its ability to acquire antibiotic resistance determinants rapidly and becoming resistant to almost all of the antibiotic classes. Borage (Echium amoenum Fisch. et Mey), is a wild annual plant of Boraginaceae family, grows in northern mountains of Iran and has largely been used by Iranian folk as a mood enhancer, anti anxiolytic, anti inflammatory, a laxative, an emollients and also it has been used for treatment of infectious diseases. So, in this study the methanolic extract of dried flowers of Echium amoenom were tested against the isolates of Acinetobacter baumannii from wound of burn patients. Materials and methods: 30 drug resistant Acinetobacter baumannii strains which were isolated from burn wounds at the Motahari hospital of Tehran were selected. Antibacterial activity of the methanolic extract was evaluated by the disc diffusion method based on CLSI protocol 2012 Results: The mean diameter of the inhibition zone for different extracts were; 9.967±6.139 mm at the concentration of 4000 ppm, at the concentration of 400 ppm 13.37±5.45 mm, 13.53±5.49 mm at the concentration of 200 ppm, 14.77±5.17mm at the concentration of 100 ppm and 14.13±5.7806mm at the concentration of 50 ppm. Conclusion: clinical strains of the A. baumannii were almost highly resistant to imipenem which is the common choice of antibiotic therapy in the hospitals. Due to the calculated p value ≤ 0.05 in this study, it can say that borage extract can be as good as or even better than the imipenem which is used in the hospitals now.